Exploring The Pragmatism of Malaysian Youth Towards Politics - Mohd Hisyamuddin Haji Basabah (Journal of Islamic World and Politics, 2024)
This article delves into the factors shaping the political inclinations of Malaysian youth, a demographic crucial for the nation's future. With youth groups representing nearly half of registered voters, their sway in elections is undeniable. They keenly observe their environment, scrutinizing policies that impact them negatively. Today's youth exhibit heightened political awareness, vital for nation-building. Political education, extending beyond elections, fosters civic engagement and societal progress. This study examines the political literacy of Malaysian youth and their pragmatic approach to politics. Through qualitative methods, including library research and interviews with 200 participants of the Sekolah Rukun Negara Program organized by the Institute of Leadership, Excellence and Development (i-LEAD), Ministry of Youth and Sports Malaysia, it explores the erosion of partisan ideologies among youth. Findings highlighted youth valuing politics for national stability and rejecting divisive racial politics. The study underscores the importance of political education in fostering unity and realizing Malaysia's national ideals.